A feasibility study on using smartphones to conduct short-version verbal autopsies in rural China. Issue 1 (December 2016) - Zhang, Jing; Joshi, Rohina; Sun, Jixin; Rosenthal, Samantha; Tong, Miao; Li, Cong; Rampatige, Rasika; Mooney, Meghan; Lopez, Alan; Yan, Lijing
Abstract Background Currently there are two main sources of mortality data with cause of death assignments in China. Both sources–the Ministry of Health-Vital Registration system and the Chinese Disease Surveillance Point system–present their own challenges. A new approach to cause of death assignment is a smartphone-based shortened version of a verbal autopsy survey. This study evaluates the feasibility and acceptability of this new method conducted by township health care providers (THP) and village doctors (VD) in rural China, where a large proportion of deaths occur in homes and cause of death data are inaccurate or lacking. Methods The Population Health Metrics Research Consortium mobile phone-based shortened verbal autopsy questionnaire was made available on an Android system-based application, and cause of death was derived using the Tariff method (Tariff 2.0); we called this set of tools "msVA." msVA was administered to relatives of the deceased by six THPs and six VDs in 24 villages located in six townships of Luquan County, Hebei Province, China. Subsequently, interviews were conducted among 12 interviewers, 12 randomly selected respondents, and five study staff to assess the feasibility and acceptability of using msVA for mortality data collection. Results Between July 2013 and August 2013, 268 deaths took place in the study villages. Among the 268 deaths, 227 VAs were completed (nine refusals, 31 migrations and one loss of data due to breakdown of the smartphone). The average time for a VA interview was 21.5 ± 3.4 min (20.1 ± 3.5 min for THP and 23.2 ± 4.1 min for VD). Both THPs and VDs could be successful interviewers; the latter needed more training but had more willingness to implement msVA in the future. The interviews revealed that both interviewers and relatives of the deceased found msVA to be feasible, acceptable, and more desirable than traditional methods. The cost of conducting a new VA was $8.87 per death. Conclusions Conduction of msVA by VDs in their own villages was feasible and acceptable in rural northern China. Broader implementation of msVA across rural China could potentially improve the coverage and quality of cause of death data, allowing for better national health evaluation and program planning.